2006
DOI: 10.1007/bf02850126
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of basal insulin from a US health system perspective: Comparative analyses of detemir, glargine, and NPH

Abstract: The purpose of this study was to compare in clinical and economic terms the long-acting insulin analogue detemir with intermediate-acting Neutral Protamine Hagedorn (NPH) insulin and with long-acting insulin glargine. Investigators used the validated Center for Outcomes Research (CORE) Diabetes Model to project clinical and cost outcomes over a 35-year base case time horizon; outcome data were extracted directly from randomized, controlled trials designed to compare detemir with NPH and with insulin glargine. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 26 publications
0
34
0
3
Order By: Relevance
“…123 Hence, potential therapeutic benefits associated with lower rates of hypoglycemic episodes and improved PPG and FPG control might be expected to offset the higher initial medication costs of insulin analogs. A number of U.S. health economic modeling studies have carried out this type of analysis comparing detemir, glargine, and NPH insulins, 124 insulin glargine and reference therapy, 125 and insulin lispro and regular insulin. 126,127 General conclusions from these studies suggest that total direct healthcare costs may be relatively similar between insulin analog and older insulin treatments, while treatment with insulin analogs may be associated with increases in quality-adjusted life expectancy.…”
Section: Cost Effectiveness Of Insulin Analogsmentioning
confidence: 99%
“…123 Hence, potential therapeutic benefits associated with lower rates of hypoglycemic episodes and improved PPG and FPG control might be expected to offset the higher initial medication costs of insulin analogs. A number of U.S. health economic modeling studies have carried out this type of analysis comparing detemir, glargine, and NPH insulins, 124 insulin glargine and reference therapy, 125 and insulin lispro and regular insulin. 126,127 General conclusions from these studies suggest that total direct healthcare costs may be relatively similar between insulin analog and older insulin treatments, while treatment with insulin analogs may be associated with increases in quality-adjusted life expectancy.…”
Section: Cost Effectiveness Of Insulin Analogsmentioning
confidence: 99%
“…16 A comparison of the direct costs of insulin detemir and insulin glargine (2006 data) indicated that costs were $2,072 less with the former (the indirect costs were also $3,103 less per patient for those receiving insulin detemir, indicating a total difference of $5,175). 16 Clinical trials.…”
Section: Tier 1: Well-validated Core Therapiesmentioning
confidence: 98%
“…In another study comparing detemir and NPH with insulin glargine, however, insulin detemir seemed to be a more attractive option [50]. The investigators used the Center for Outcomes Research Diabetes Model to project clinical and cost outcomes over 35 years, with data extracted from randomized, controlled trials.…”
Section: Cost Of Treatmentmentioning
confidence: 99%